Facile approach to diverse range of 1,3-diaza-heterocycles: angular/linear selectivity paradigm and a remarkable intramolecular methyl migration - Kshirsagar, Umesh A.; N. P. Argade (Tetrahedron, 2009)
Starting from cyclic anhydrides and tert-butyl 2-aminobenzylcarbamate, simple and efficient synthesis of diverse range of kinetically controlled angular and thermodynamically controlled linear tricyclic and tetracyclic 1,3-diaza-heterocycles have been described via the intramolecular cyclizations of the corresponding imides/anilic acid esters. The effect of imide stability on the angular/linear product selectivity has also been described. The kinetically controlled angular products were successfully transformed to the corresponding thermodynamically controlled linear products by refluxing in methanol or methanol and acetic acid mixture. An interesting in situ 1,2-intramolecular methyl group migration has also been described. (C) 2009 Elsevier Ltd. All rights reserved.